HUBUNGAN LAMA PEMAKAIAN KB SUNTIK 3 BULAN DENGAN TERJADINYA HIPERMENOREA DI TPMB Bd. SRI HERLINANI, S.ST KECAMATAN RANDUAGUNG KABUPATEN LUMAJANG - Mutrisia, Bintari Luqi; Rohmatin, Homsiatur; Farianingsih, Farianingsih (NHM PRESS, 2023)
Such rapid population growth can cause various problems in society. In an effort to deal with population growth which is quite fast, the government is promoting the Family Planning (KB) program. Sri Herlinani, S.ST, Randuagung District, Lumajang Regency. The research method used is correlation analysis with a cross sectional approach. All acceptors of 3-month injection KB users at TPMB Bd. Sri Herlinani, S.ST, Randuagung, Lumajang in May 2023 there were 40. Respondents were taken using the total sampling technique, the test used was Chi-Square. The results showed that most of the respondents with a duration of 3 months > 1 year of family planning had hypermenorrhea, 16 people (40%). The results of the analysis using SPSS obtained p value = 0.034 < α = 0.05. The conclusion is that there is a long-term relationship with the use of a 3-month injection KB with the occurrence of hypermenorrhea in TPMB Bd. Sri Herlinani, S.ST, Randuagung, Lumajang. Midwives are required to provide counseling about the advantages and side effects of family planning and how to deal with side effects if there are side effects from 3-month injection birth control, so that acceptors are not worried if side effects occur (hypermenorrhea).